دور الجامعات السعودية في تعزيز ثقافة التعليم عن بعد في ظل جائحة كورونا وتداعياتها على تحقيق الهدف 4 للتنمية المستدامة - فرج، علياء عمر كامل إبراهيم (جامعة بنها - كلية التربية, 2022)
هدفت الدراسة الحالية إلى بيان دور الجامعات السعودية في تعزيز ثقافة التعليم عن بعد في ظل جائحة كورونا بين طلابها، وكشفت المعوقات التي تواجه أعمال ثقافة التعليم عن بعد وانعكاسها على تحقيق الهدف ٤ للتنمية المستدامة، وآليات تفعيلها، وتحقيقًا لذلك اتبعت الدراسة المنهج الوصفي، وتمثلت الأداة في استبانة تكونت بصورتها النهائية من (٣٠) فقرة وزعت على ثلاثة محاور، وطبقت على عينة عشوائية من طلبة الجامعات السعودية بكل من (جامعة الأمير سطام بن عبد العزيز، جامعة القصيم وجامعة شقراء) بلغت (٤٦٠) طالبًا وطالبة، وخلصت الدراسة إلى أن ممارسة الجامعات السعودية لدورها في تعزيز ثقافة التعليم عن بعد في ظل جائحة كورونا بشكل عام جاءت مرتفعة، وبالنسبة للمحاور؛ حصل محور تداعيات تعزيز ثقافة التعليم عن بعد في ظل جائحة كورونا على تحقيق الهدف 4 للتنمية المستدامة على أعلى متوسط (٣.٩٧)، يليه محور واقع دور الجامعات السعودية في تعزيز ثقافة التعليم عن بعد في ظل جائحة كورونا وحصل على متوسط عام (3.89) أي بدرجة مرتفعة، وأخيرًا محور معوقات إعمال ثقافة التعليم عن بعد في ظل جائحة كورونا وحصل على متوسط (3.70) وجميعها بدرجة مرتفعة، وأوضحت النتائج أنه لا توجد فروق دالة إحصائيًا بين تقديرات أفراد الدراسة تعزى إلى متغيرات (الكلية والبرنامج الدراسي)، في حين توجد فروق دالة تعزى إلى متغيرات (النوع ومحل الإقامة)، وأوصت الدراسة بضرورة نشر ثقافة التعليم عن بعد في الجامعات السعودية بين طلابها، وإنشاء محتوى رقمي تفاعلي يقدمه أعضاء هيئة التدريس المؤهلون تكنولوجيًا لخلق جيل يمكنهم التعامل مع المستحدثات المختلفة. The current study aimed to clarify the role of Saudi universities in promoting the culture of distance Learning in light of the Corona pandemic among their students, and to reveal the obstacles facing the work of the culture of distance Learning and their reflection on achieving Goal 4 for sustainable development, and to achieve this, the study follows the descriptive approach. The tool was represented in a questionnaire consisting in its final form of (30) paragraphs distributed on three axes, and it was applied to a random sample of Saudi university students in (Prince Sattam bin Abdul-Aziz University, Qassim University and Shaqra University) amounting to (460) male and female students, The study concluded that the practice of Saudi universities for their role in promoting the culture of distance Learning in light of the Corona as for the axes; The axis of the ‘pandemic in general was high repercussions of promoting a culture of distance Learning in light of the Corona pandemic achieved the achievement of Goal 4 for sustainable development, with the highest average (3.97), It is followed by the reality of the role of Saudi universities in promoting the culture of distance Learning in light of the Corona pandemic, and it obtained an Finally, the axis of ‘overall average of (3.89) that is, to a high degree obstacles to implementing the culture of distance Learning in light of the Corona pandemic, and it obtained an average of (3.70), all of which are at a high degree, the results showed that there are no statistically significant differences between the estimates of the study members due to the variables (college and study programme), while there are significant differences due to the variables (gender and place of . The study recommended the need to spread the culture of Residence distance education in Saudi universities among their students, and to create interactive digital content provided by technologically qualified faculty members to create a generation that can deal with various innovations.
Keywords: التعليم الجامعي -- التعليم عن بعد -- جائحة كورونا "كوفيد-19" -- التنمية المستدامة -- الجامعات السعودية